ANALISIS NILAI PANCASILA YANG TERKANDUNG DALAM TRADISI BATOBO DI DESA TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Yuhartika Aprilianti; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this reaserchis motivated by the mutual cooperation as a characteristic of the Indonesian nation that has been passed down for generation which is listed in the third principle of Pancasila namely the unity of Indonesian. The mutual cooperation character in Riau region is initialy driven by traditional leader’s policies in fostering their generation in achieving unity and entity in community life. The same as the tradition of Batobo which is carried out by malay people, especially in Kuantan Singingi district which has been carried out for generation. The formulation of the problem in this research is to find out wheter there Pancasila values in the Batobo tradition in Teluk Beringin village, Gunung Toar subdistrict Kuantan Singingi district. The population in this reaserch is the people of Teluk Beringin village. While the sampling technique used is purposive sampling technique which is as many as 16 people from Tobo group members and Ninik Mamak who understand more about the Batobo tradition in Teluk Beringin village, Gunung Toar subdistrict, Kuantan Singingi district. The data collection technique in tihs reaserch are observation, questionnaires, interviews, and documentation. The data analysis technique used in this reaserch is descriptive quantitative by using the formula P = F/N x 100%. Based on the result of the reaserch, it can be concluded that from 16 respondents in the procession before going down to the field or rice field the respondents who state Yes that Batobo tradition contains the values of Pancasila is 95,5%, who state No is 4,5%, then when they are going down to the field or rice field. The respondents who state Yes that batobo tradition contains the values of Pancasila is 67,2%, who state No is 32,8%, and after going down to the field or rice field the respondent who state Yes is 100%, and who state No is 0%. So this reaserch proves that in the Batobo tradition in Teluk Beringin village, Gunung Toar subdstrict Kuantan Singingi district is contained the Pancasila values.Key Words: Pancasila Values, Batobo Tradition